(untitled) (River Edge, NJ, 2004)
This book presents the experience of coastal and port engineering development, as well as coastal environmental problems, in Asian and Pacific countries. It also provides information and promotes technological progress and activities, international technical transfer and cooperation, and opportunities for engineers and researchers to maintain and improve scientific and technical competence. The subject areas are not limited to the classical topics of coastal engineering but are extended to related fields, including environments, marine ecology, coastal oceanography, fishery, etc.
Keywords: Coasts,Geology, Structural,Oceanography,Bờ biển; Asia,Pacific Ocean,Pacific Ocean,Châu Á